A Nau do século XXI: o brinquedista no espaço do brincar - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The Nautical Chart traces clues in the construction of the paths of the trip to analyze the constructive elements to the formation of the Virtual Toys in general in the discipline Games and play activities and in a specific way in the "Space of the Play". The route of the trip with the approach of cartographic and qualitative inspiration there is no separation between knowing and doing. We unmasked the Port of Origin, in the teaching internship, in the group of the 5th Period 2017/1 of the Pedagogy Course of the Faculty of Education of the Federal University of Amazonas. The challenge was to keep the thinking open, without preconceptions, to follow processes and to be guided by the events. This movement led us to the First Scale, Discipline Games and Play Activities, where the concepts, theoretical references about games, games and play activities were our focus. So the problem has arisen: does the discipline games and play activities encourage building elements to the formation of a toy? With the targeted focus, it is possible to identify the organizing strategies of the teaching and learning processes. Navigating is necessary towards the Port of Destiny where we inhabit the territory "Espaço do Brincar", mapping it and drawing lines that express its possibilities and potential of pedagogical mediation. By including in the territory, composing the landscape of the trip, accompanying rhythms and processes, we did the Anchoring reflecting on the tracks built in the path of the trip pointing out possible lines to make explicit the constructive elements to the formation of the Virtual Toys.
The Nau of the 21st century: the toy in the playground
Keywords: Jogos educativos; Brinquedoteca; Ambiente virtual de aprendizagem; CIÊNCIAS HUMANAS: EDUCAÇÃO: ENSINO-APRENDIZAGEM: MÉTODOS E TÉCNICAS DE ENSINO